2005
DOI: 10.1037/0012-1649.41.1.235
|View full text |Cite
|
Sign up to set email alerts
|

Friendship Jealousy in Young Adolescents: Individual Differences and Links to Sex, Self-Esteem, Aggression, and Social Adjustment.

Abstract: Children's vulnerability to jealousy surrounding their best friends was explored in 2 studies. Study 1 involved 94 adolescents who reported on their friendship jealousy on a newly created measure. Results indicated that the jealousy measure had sound psychometric properties and produced individual differences that were robust over time and free from socially desirable responding. As expected, girls and adolescents with low self-worth reported the greatest friendship jealousy. Study 2 involved 399 young adolesc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
161
3
9

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 164 publications
(179 citation statements)
references
References 64 publications
6
161
3
9
Order By: Relevance
“…Recent research with late childhood and early adolescent youth also examines whether girls feel more jealousy than boys over their friends' relationships with others. The findings are not completely consistent, with sex differences emerging in some cases but not others (Parker, Low, Walker, & Gamm, 2005;Roth & Parker, 2001). However, the effect sizes tend to favor girls, and may be especially large when classmates' reports are used as compared to when self report or friend reports are used .…”
Section: Social-cognitive Styles-mentioning
confidence: 93%
See 1 more Smart Citation
“…Recent research with late childhood and early adolescent youth also examines whether girls feel more jealousy than boys over their friends' relationships with others. The findings are not completely consistent, with sex differences emerging in some cases but not others (Parker, Low, Walker, & Gamm, 2005;Roth & Parker, 2001). However, the effect sizes tend to favor girls, and may be especially large when classmates' reports are used as compared to when self report or friend reports are used .…”
Section: Social-cognitive Styles-mentioning
confidence: 93%
“…Moreover, evidence supports relations between some aspects of social-cognitive style and indexes of adjustment (e.g., LaGreca et al, 1988;LaGreca & Lopez, 1998;Parker et al, 2005). However, little empirical data actually test whether sex-linked social-cognitive styles mediate sex differences in emotional and behavioral adjustment.…”
Section: Social-cognitive Stylesmentioning
confidence: 99%
“…This work largely focuses on protective functions of friendships, such as providing companionship, reliable alliances, and validation (Asher & Parker, 1989;Newcomb & Bagwell, 1995;Sullivan, 1953). Recently, more attention has been paid to the risks of friendships, such as those related to having deviant friends (e.g., Brendgen, Vitaro, & Bukowski, 2000) or experiencing jealousy in friendships (Parker, Low, Walker, & Gamm, 2005). In contrast to work that examines either protective or risk factors, very little attention has been paid to the idea that some friendship processes have both costs and benefits (Rose & Rudolph, 2006).…”
Section: The Influence Of Friendship Processes On Adjustmentmentioning
confidence: 99%
“…Marsh, Allen, Ho, Porter, and McFarland ( 2006 ) demonstrated that, over time, early adolescents with high levels of ego development are more successful in forming close attachments to friends, establishing intimate friendships, and achieving a high level of (sociometric) popularity among peers. However, Parker, Low, Walker, and Gamm ( 2005 ) traced inclinations toward and reputations for jealousy in friendships among White, lower to middle -class rural early adolescents in the United States. Feelings of jealousy exacerbated a sense of loneliness, even among those who lacked friends and were not well liked.…”
Section: Friendship Motives and Expectationsmentioning
confidence: 99%